Mortalidade Materna: uma abordagem atualizada - Viana, Rosane da Costa; Novaes, Maria Rita Carvalho Garbi; Calderon, Iracema de Mattos Paranhos [UNESP] (My University, 2011)
Purpose: to review literature, highlighting current aspects of maternal mortality.  Method: research initiated through electronic data base PubMed [http:// www.ncbi.nlm.nih.gov/pubmed], limited to the last 10 years. The selected cases which related to pre-defined aspects of interest to the study, such as vulnerable population, risk factors, causes, difficulties in obtaining data, preventive measures e new approaches to the problem, among them, ‘near misses’ and severe maternal morbidity.  Results: maternal death is directly related to the quality of life of the population, with relevant disparities among the different social economic areas. Although maternal mortality is the proper indicator to the female population health, its numbers are presented in unrealistic manners due to the difficulties in identifying the cases through death certificates. Preventive measures associated to early and adequate diagnose and treatment are benefic factors in decreasing those maternal deaths. Apart from these, identification and classification of ‘near misses’ and maternal morbidity are featured in the contemporary approach to the issue.  Final considerations: In spite of advanced technology and recognition of preventive measures, a large number of women die daily due to complications in the pregnancy and puerperal cycle. To decrease such tragedy political, social and economical commitment to Health is necessary, in order to promote the needed reforms in the assistance of such cycle.

Objetivos: Realizar uma revisão da literatura, destacando aspectos atuais da mortalidade materna. Método: A pesquisa foi iniciada pela base eletrônica PubMed [http:// www.ncbi.nlm.nih.gov/pubmed], limitada aos últimos 10 anos. Foram selecionados os que abordavam aspectos pré-definidos, de interesse à proposta do estudo - a população vulnerável, os fatores de risco, as causas, as dificuldades para obtenção dos dados, as medidas de prevenção e as novas abordagens do problema, entre elas, “near miss” e morbidade materna grave. Resultados: O óbito materno está diretamente relacionado com as condições de vida da população, com disparidade importante entre as diversas regiões socioeconômicas. Embora a mortalidade materna seja o melhor indicador de saúde da população feminina, seus números são apresentados de forma irreal, pela dificuldade na identificação dos casos nos registros de óbito. Medidas de prevenção associadas a diagnóstico e tratamento precoces e adequados são fatores benéficos na redução desses óbitos maternos. Além destes, a identificação e classificação dos casos de “near miss” e morbidade materna grave ganham destaque na abordagem atual do problema. Considerações finais: Apesar da tecnologia avançada e do reconhecimento de algumas medidas de prevenção, um grande número de mulheres morre diariamente por complicações no ciclo gravídico-puerperal. Para reduzir esta tragédia é necessário o comprometimento político, social e econômico com a saúde, para promover as reformas necessárias na assistência ao ciclo gravídico-puerperal.
Maternal Mortality: an update approach
Keywords: Maternal mortality; Epidemiology; Determinant factors; Grave maternal morbidity; Mortalidade materna; Morbidade materna grave; Near miss